Reparación ósea: rol de las isoflavonas en los procesos celulares involucrados - Cepeda, Sabrina Belén (2017)
Phytoestrogens (PE) as isoflavone Genistein (Gen) are dietary supplements proposed to reduce the risk of osteoporotic fractures in postmenopausal women. After healing, bone repair depends on angiogenesis that supplies preosteoblasts and factors required for osteoblasts (OB) differentiation, bone formation and mineralization. New capillaries formation involves EC proliferation; migration as well as synthesis of VEGF. Bone remodeling can also be induced by biocompatible silica nanoparticles (NPMsi) capable to generate neo extracellular bone matrix. We previously demonstrated that Gen stimulates bone cells differentiation through its direct action on vascular tissue. In this work we evaluated the role of Gen on the cellular events involved in bone repair. Experimental model: aortic rings (AR); primary cell cultures of aortic endothelial cells (EC) or calvaria OB isolated from female Wistar rats aged 1 to 3 weeks. In vitro treatments with Gen (1 nM-5 ìM) during 24-72 h were performed. PE stimulated EC proliferation in all range of concentrations employed (22-39% above control, p <0.01). Indeed, Gen increased the expression of the proangiogenic factor VEGF measured by immunoassay (1 fold, p <0.001). Whether the angiogenic action of Gen depends on bone vascular (B-V) interactions was also evaluated. To that end, assays were performed using conditioned medium (CM) obtained from OB cell cultures treated with Gen (24h). The presence of CM induced a 3 fold (p <0.05) increase in EC migration respect to Gen treatment in the absence of CM. Angiogenesis was measured as new capillaries formation using AR seeded in a protein matrix for 5 days in the presence or absence of CM. Tubes formation was quantified by optic microscopy. In the presence of CM, the AR exhibited a greater number of three-dimensional tubular structures around the rings. Finally, the role of Gen on OB differentiation in the presence of NMPs of silica was evaluated. Alkaline phosphatase activity and extracellular calcium deposition (Alizarin staining) were measured as OB differentiation markers. NMPsi + Gen co-treatment enhanced both markers (p <0.002) with an additive action respect to NMPs alone. In conclusion, Gen elicited a positive regulation of the cellular processes involved in the bone repair through B-V interaction, and also favors the action of tissue regeneration biomaterials.